2022
DOI: 10.3389/fmed.2022.796165
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Predisposition to Coronavirus Disease 2019 in Relation to Ten Cardiovascular Conditions: A Two-Sample Mendelian Randomization Study

Abstract: BackgroundThe long-term health consequences of coronavirus disease 2019 (COVID-19) remain largely unclear. This study aimed to apply the Mendelian randomization (MR) design to estimate the causal associations between COVID-19 and ten cardiovascular conditions.MethodsSingle-nucleotide polymorphisms (SNPs) associated with COVID-19 were used as instrumental variables to estimate the causal effect of COVID-19 on ten cardiovascular conditions. The random-effects inverse-variance weighted (IVW) method was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Existing GWAS related to this topic suffer from small sample sizes and focus primarily on critically ill COVID-19 patients which supports the causal association [34]. Moreover, current GWAS ndings are inconsistent, with some studies suggesting that there is no relationship between genetically instrumented COVID-19 and the risk of HF [35].…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Existing GWAS related to this topic suffer from small sample sizes and focus primarily on critically ill COVID-19 patients which supports the causal association [34]. Moreover, current GWAS ndings are inconsistent, with some studies suggesting that there is no relationship between genetically instrumented COVID-19 and the risk of HF [35].…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Notably, these results were based on observational studies. Recently, several studies used the Mendelian randomization design to show the causal associations between COVID-19 infection and cardiovascular risk factors, including hypertension, coronary heart disease, heart failure, and ischemic stroke (5)(6)(7). One previous study indicated that patients with severe COVID-19 were more likely to have the cerebrovascular disease (2.3 vs. 1.2%) (8).…”
Section: Introductionmentioning
confidence: 99%